2003
DOI: 10.1093/jaoac/86.4.759
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Chromatographic Determination of α-Solasonine in Frozen Green Peas as an Indicator of the Presence of Nightshade Berries

Abstract: Nightshade berries containing glycoalkaloids can be a contaminant in green peas. Methodology was developed to detect this contamination. The glycoalkaloid α-solasonine was extracted from frozen green peas with 1% (v/v) acetic acid, cleaned up on a C18 cartridge, and determined by liquid chromatography with UV detection at 200 nm. Method performance characteristics for the determination of α-solasonine include linearity from 140 to 1500 ng injected (r = 0.9996–0.9999); recovery ranging from 68 to 79%; limit of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The potential of S. nigrum and the related species S. ptycanthum Dun (eastern black nightshade) to contaminate food crops, such as beans, peas and soybeans, is a problem noted by several authors (Eldridge and Hockridge, 1983;Ogg et al, 1981;Ogg and Rogers, 1989). Cavlovic et al (2003) reported unripe berries of S. nigrum to contain 1,100 mg/kg fw a-solasonine and 900 mg/kg fw a-solamargine. In a follow-up of the RASFF notification 2013.0804, six samples of S. nigrum green berries were analysed by LC-MS/MS (P. Mulder, 2019, personal communication).…”
Section: Occurrence Data On Gas In Other Food Productsmentioning
confidence: 99%
“…The potential of S. nigrum and the related species S. ptycanthum Dun (eastern black nightshade) to contaminate food crops, such as beans, peas and soybeans, is a problem noted by several authors (Eldridge and Hockridge, 1983;Ogg et al, 1981;Ogg and Rogers, 1989). Cavlovic et al (2003) reported unripe berries of S. nigrum to contain 1,100 mg/kg fw a-solasonine and 900 mg/kg fw a-solamargine. In a follow-up of the RASFF notification 2013.0804, six samples of S. nigrum green berries were analysed by LC-MS/MS (P. Mulder, 2019, personal communication).…”
Section: Occurrence Data On Gas In Other Food Productsmentioning
confidence: 99%